Wet Cupping Therapy to Reduce Total Cholesterol Levels in People with Diabetes - Hapipah Hapipah; M Iwan Zulhan; Bahjatun Nadrati (Universitas Nahdlatul Ulama Surabaya, 2022)
Diabetes Mellitus is a condition characterized by an increase in blood glucose levels, accompanied by metabolic abnormalities. Increased blood sugar levels in DM can cause cholesterol levels in the blood to increase, causing atherosclerosis. Management of high cholesterol levels in DM patients is needed to prevent complications. One of non-pharmacological therapy that can be used in DM patients with high cholesterol levels is cupping therapy. The purpose of this study was to determine the effect of cupping therapy on reducing cholesterol levels in patients with diabetes mellitus in Mantang Public Health Center. The type of research used is quasi experimental with one group pretest posttest design. The number of samples as many as 16 people taken by simple random sampling technique. This research was conducted in April-June 2019 in 3 villages in Batukliang District. Statistical test using paired t test on cholesterol levels before and after the intervention obtained a significance value of 0.000 (p-value <0.05) so that it can be concluded that there is a significant effect between cupping therapy and cholesterol levels in patients with diabetes mellitus. This research can be used as a nursing action for complementary treatment in DM patients with high cholesterol levels.